Effect of tea intake on genetic predisposition to gout and uric acid: a Mendelian randomization study - Yu, Yunfeng; Yang, Xinyu; Hu, Gang; Tong, Keke; Yin, Yuman; Yu, Rong (Frontiers in Endocrinology, 2024)
The effect of tea on gout and uric acid is still controversial. This study aims to analyze the effect of tea intake on genetic predisposition to gout, idiopathic gout, gout due to impairment of renal function as well as uric acid by Mendelian randomization (MR). Methods: Forty independent single nucleotide polymorphisms (SNPs) associated with tea intake were selected from UK Biobank. SNPs for uric acid were obtained from BioBank Japan, SNPs for gout were obtained from UK Biobank, and SNPs for gout due to impairment of renal function and idiopathic gout were derived from FinnGen. The causal relationship of exposure-outcome was tested using inverse variance weighted, MR-Egger and weighted median. MR-Egger intercept was employed to assess data multiplicity, Cochran's Q test was used to assess heterogeneity, and leave-one-out sensitivity analysis was utilized to analyze the stability of the results. Results: The results of MR analysis showed that tea intake was negatively associated with gout due to impairment of renal function (OR 0.997, 95% CI 0.994 to 0.999, P = 0.017), whereas there was no causal association with gout, idiopathic gout, and uric acid (P > 0.05), for which sensitivity analysis suggested that these results were robust. Conclusions: There was a genetic predisposition effect of increased tea intake on the reduced risk of gout due to impairment of renal function, whereas there was no such effect on gout, idiopathic gout, and uric acid. Tea intake may become an important option in the dietary treatment of gout due to impairment of renal function.